2009
DOI: 10.1111/j.1420-9101.2008.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Senescent sperm performance in old male birds

Abstract: Senescence is the deterioration of the phenotype with age caused by negative effects of mutations acting late in life or the physiological deterioration of vital processes. Birds have traditionally been assumed to senescence slowly despite their high metabolic rates, high blood sugar levels and high body temperature. Here we investigate the patterns of age‐related performance of sperm of a long distance migrant, the barn swallow Hirundo rustica, varying in age from 1 to 6 years, analysed by the computer‐assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 52 publications
5
50
1
Order By: Relevance
“…Since sperm traits of male birds tend to degrade with age (Møller et al 2009), it is unlikely that these young females selectively copulated with older EP males to assure fertilization, unless sperm transfer improves with male age. It is more likely that young females assigned paternity to EP males older than their partners to obtain better genes for their offspring, consistent with predictions from life history theory (Manning 1985;Kokko 1998;Brooks and Kemp 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Since sperm traits of male birds tend to degrade with age (Møller et al 2009), it is unlikely that these young females selectively copulated with older EP males to assure fertilization, unless sperm transfer improves with male age. It is more likely that young females assigned paternity to EP males older than their partners to obtain better genes for their offspring, consistent with predictions from life history theory (Manning 1985;Kokko 1998;Brooks and Kemp 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, sperm morphology, sperm velocity, and the relationships between sperm traits may vary according to male age and sexual activity. In addition, recent studies have shown that sperm quality decreases as males get older (Dean et al 2007;Pizzari et al 2008b;Møller et al 2009), and male age may thus confound the relationships between sperm morphology, velocity, and motility through senescence processes. How social status, male age, and male sexual activity relate to sperm characteristics in the house sparrow still remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Møller et al 2009). Chick provisioning is also shared with the male, but little is known about age-specific provisioning behaviour in male or female birds.…”
Section: K1mentioning
confidence: 99%